1958
DOI: 10.1017/s001675680006297x
|View full text |Cite
|
Sign up to set email alerts
|

The Compositions of Coexisting Pyroxenes in Metamorphic Assemblages

Abstract: Chemical and optical data are provided on pyroxene pairs in a range of metamorphic assemblages. Tie line trends in the system CaSiO3–MgSiO3–FeSiO3 for these assemblages are compared with those recorded for plutonic igneous associations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1960
1960
1974
1974

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…Thus, we note that all three olivine-bearing granulites shown in Table 2 of Muir and Tilley (1958) show consistent " anomalies" [tie-line intersections (chemical) on Mg-Ca line for Nos. 2, 48, and 4 (my numbers) are XMg8, XMg5, and XMg3, respectively-see Table 5, this paper].…”
Section: Possible Causes Of " Anomalies " In the Trends Of Optically mentioning
confidence: 56%
See 1 more Smart Citation
“…Thus, we note that all three olivine-bearing granulites shown in Table 2 of Muir and Tilley (1958) show consistent " anomalies" [tie-line intersections (chemical) on Mg-Ca line for Nos. 2, 48, and 4 (my numbers) are XMg8, XMg5, and XMg3, respectively-see Table 5, this paper].…”
Section: Possible Causes Of " Anomalies " In the Trends Of Optically mentioning
confidence: 56%
“…I believe that there is insufficient evidence available to say that there is no significant chemical difference between co-existing pyroxenes from the hornfelses and those from the metamorphic rocks of granulite facies. Muir and Tilley (1958) publish chemical data of three hornfelses (Nos. 1, 2, and 48), and another has recently come to hand (No.…”
Section: Possible Causes Of " Anomalies " In the Trends Of Optically mentioning
confidence: 99%
“…The orthopyroxene of this rock has a higher iron to magnesium ratio than the clinopyroxene, as is normal in igneous rocks, and in metamorphic rocks of the granulite and pyroxene hornfels facies (Muir and Tilley, 1958). The amphibole associated with these pyroxenes has a higher iron to magnesium ratio than either, which also appears to be normal in granulite facies assemblages, other than very magnesian ones (Buddington, 1952;Howie, 1955), but contrary to predictions from experimental data (Bowen and Schairer, 1935 (a)).…”
mentioning
confidence: 78%
“…However, the tie-lines of pyroxenes analysed by Ross, Foster, and Myers, when extended, intersect the Ca-Fe side line at Fs2.7, the clinopyroxenes being unique in having a higher Fe/(Fed-Mg) ratio than the associated orthopyroxenes. Muir and Tilley (1958) noted that pyroxenes from volcanic rocks have their cliuopyroxenes relatively enriched in iron, a relation corresponding to a non-equilibrium condition, while O'Hara (1960) suggested that differences in the distribution of Ca, Mg, and Fe are probably due in part to variations in the conditions of formation. Brown (1961) demonstrated that in coexisting igneous pyroxene pairs the orthopyroxene is enriched in Fe/(Fe-t-Mg) relative to the elinopyroxene, usually causing the tie-line to intersect the Ca-Mg side of the triangular diagram.…”
Section: 184mentioning
confidence: 99%